Moderasi Thin Capitalisation atas Faktor-Faktor yang Memepengaruhi Penghindaran Pajak Pada Perusahaan Manufaktur ASEAN - Tambun, Sihar; Saputra, Winnendra Dwi (Universitas 17 Agustus 1945 Jakarta, 2024)
This study aims to analyze the influence of liquidity, earnings management, and ownership of intangible assets on tax avoidance, moderated by thin capitalisation. The research uses secondary data from manufacturing companies listed on the stock exchanges of ASEAN countries for the period 2018-2022, with a sample of 2.225 financial statements. Utilizing Stata (version 15) and Microsoft Excel 2019 applications, the data analysis methods in this study include descriptive statistics, multiple linear regression with panel data, and moderated regression analysis. The study concludes that liquidity has no significant effect on tax avoidance, whereas earnings management and ownership of intangible assets have a significant positive effect on tax avoidance. Additionally, thin capitalisation cannot moderate the effect of liquidity on tax avoidance but can strengthen the positive effect of earnings management and ownership of intangible assets on tax avoidance.